PENERAPAN DIGITAL LEADERSHIP DALAM MENDORONG INOVASI DAN KREATIVITAS SDM DI SEKTOR PARIWISATA - Dewi, Irra Chrisyanti (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The study investigates the impact of digital leadership on the innovation and creativity of human resources (HR) within the tourism sector, employing a survey-based quantitative approach. Digital transformation in this industry necessitates leaders who can effectively integrate technology to foster an innovative and creative work environment. Data were collected through questionnaires distributed to 120 respondents, comprising managers and employees from various tourism organizations across different regions. The analysis utilized linear regression to explore the relationships between the variables of digital leadership, innovation, and HR creativity. The results indicate that digital leadership exerts a positive and significant influence on both HR innovation and creativity. Specifically, digital leaders who empower their employees through technology, maintain effective communication, and encourage continuous learning play a crucial role in fostering creative ideas and implementing innovations within their organizations. These findings offer valuable insights for stakeholders in the tourism industry, suggesting that adopting effective digital leadership strategies can enhance competitiveness. By prioritizing digital leadership, organizations can better navigate the challenges posed by rapid technological advancements and changing market demands. In conclusion, the study underscores the essential role of digital leadership in driving innovation and creativity among HR in the tourism sector. As the industry continues to evolve with digital transformation, leaders must adapt their strategies to cultivate an environment conducive to creativity and innovation, ultimately contributing to organizational success. Keywords: Digital Leadership; Innovation; Creativity; Tourism; Human Resources